2020
DOI: 10.3390/en13112935
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Control of Supercritical and Ultra-Supercritical Power Plants: A Review

Abstract: This paper presents a critical review of the research conducted for modeling and controlling supercritical power plants. Thermal power plants are classified according to the boiler pressure to supercritical and subcritical. The modeling concepts and control strategies of supercritical generation units are far more complex than those of subcritical. On the other hand, supercritical generation technologies are more efficient and much cleaner than subcritical generation units. From a deep technical analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 70 publications
0
26
0
Order By: Relevance
“…Supercritical power plants have higher thermal efficiency, stable combustion, better fuel economy, reduced emissions, faster load following response than the sub-critical power plants, and are generally employed for electrical power generation systems [57].…”
Section: Overview Of a Coal Power Plant Operationmentioning
confidence: 99%
“…Supercritical power plants have higher thermal efficiency, stable combustion, better fuel economy, reduced emissions, faster load following response than the sub-critical power plants, and are generally employed for electrical power generation systems [57].…”
Section: Overview Of a Coal Power Plant Operationmentioning
confidence: 99%
“…Various articles have been presented in the field of thermal management in industries [3][4][5]. Here are some of the latest ones.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of reviews in the literature are either excessively comprehensive or comparative. However, Mohamed et al (2020) [29] provided a recent critical review on supercritical and ultra-supercritical power plant modeling and control, with an emphasis on the model-based control of SCPP. The advantages are objectively reviewed, as is the supercritical process, the modeling methodologies utilized for these kinds of plants, the control tactics, and lastly, some issues that may be addressed for future studies that may bring advances to this field are suggested.…”
Section: Control System Reviewmentioning
confidence: 99%